Application of the new GOLD COPD staging system to a US primary care cohort, with comparison to physician and patient impressions of severity - Mapel DW (International Journal of COPD, 2015)
Douglas W Mapel,1 Anand A Dalal,2 Phaedra J Johnson,3 Laura K Becker,3 Alyssa Goolsby Hunter3 1Epidemiology and Health Outcomes Research, Lovelace Clinic Foundation, Albuquerque, NM, 2US Health Outcomes and Medical Policy, GlaxoSmithKline, Research Triangle Park, NC, 3Life Sciences, Optum, Eden Prairie, MN, USA Background: In 2011, the traditional Global Initiative for Chronic Obstructive Lung Disease (GOLD) COPD spirometry-based severity classification system was revised to also include exacerbation history and COPD Assessment Test (CAT) and modified Medical Research Council Dyspnea Scale (mMRC) scores. This study examined how COPD patients treated in primary care are reclassified by the new GOLD system compared to the traditional system, and each system’s level of agreement with patient’s or physician’s severity assessments. Methods: In this US multicenter cross-sectional study, COPD patients were recruited by 83 primary care practitioners (PCPs) to complete spirometry testing and a survey. Patients were classified by the traditional spirometry-based system (stages 1–4) and under the new system (grades A, B, C, D) using spirometry, exacerbation history, mMRC, and/or CAT results. Concordance between physician and patient-reported severity, spirometry stage, and ABCD grade based on either mMRC or CAT scores was examined. Results: Data from 445 patients with spirometry-confirmed COPD were used. As compared to the traditional system, the GOLD mMRC system reclassifies 47% of patients, and GOLD CAT system reclassifies 41%, but the distributions are very different. The GOLD mMRC system resulted in relatively equal distributions by ABCD grade (33%, 22%, 19%, 26%, respectively), but the GOLD CAT system put most into either B or D groups (9%, 45%, 4%, and 42%). The addition of exacerbation history reclassified only 19 additional patients. Agreement between PCPs’ severity rating or their patients’ self-assessment and the new ABCD grade was very poor (κ=0.17 or less). Conclusion: As compared to the traditional system, the GOLD 2011 multidimensional system reclassified nearly half of patients, but how they were reclassified varied greatly by whether the mMRC or CAT questionnaire was chosen. Either way, the new system had little correlation with the PCPs or their patients’ impressions about the COPD severity. Keywords: assessment, comorbidity, exacerbation, Global Initiative for Chronic Obstructive Lung Disease, spirometry, stratification